Rola i pozycja kobiety w staropolskich ekonomikach - Agnieszka Korczyńska (In Gremium. Studies in History, Culture and Politics, 2016)
WOMAN'S ROLE AND POSITION IN OLD-POLISH BOOKSThe article investigates the role and position of a woman in Sarmatian culture, which is one of the most characteristic periods in Polish history. Those days it was assumed that Polish gentry stems from an Ancient brave Sarmatian people. A real Old-Polish noblemen was a devoted Catholic who strongly propagated family and social ties. However, how was an ideal Sarmatian woman depicted? Was her position in the family hierarchy lower, equal or higher than the man’s?Undeniably, in literature, female portrait was frequently being omitted. It was not until the 16th century that the word “woman” began to occur in the works of Old-Polish writers. In this work the perfect picture of a lady, presented in Old-Polish books, has been taken under closer inspection. These images influenced consciousness creation of Sarmatian society. The analysis is based on putting Old-Polish books in chronological order, and then characteristic descriptions of a woman have been identified in the texts. Finally, the layout of the article has been divided into three parts: woman as a mother, woman as a wife and woman as a housewife.